A Comprehensive Study on Tetraaryltetrabenzoporphyrins. Issue 15 (25th February 2020) - Ruppel, Michael; Lungerich, Dominik; Sturm, Sabrina; Lippert, Rainer; Hampel, Frank; Jux, Norbert
Abstract: Invited for the cover of this issue are the groups of Lungerich and Jux at the Friedrich‐Alexander University Erlangen‐Nuernberg. The image depicts the synthetic feasibility with a "TATBP tuning shop", which shows the change of the four meso aryl substituents to modify the performance of the molecule. Read the full text of the article at 10.1002/chem.201904718 . Abstract : " To our surprise, we have achieved [a high‐yielding synthetic protocol] for tetraaryltetrabenzoporphyrins, which allowed us to perform our comprehensive study of this compound class ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3287 ff. (DOI: 10.1002/chem.201904718 ).